Discover and educate the emotions through games and sport activities - Coco, Daniele (Formazione & insegnamento, 2017)
Natural changes that everyone experiences in a lifetime can be characterized by moments of crisis and inability in managing emotions. The recreational and sport practices can be a pathway towards knowledge of one’s emotions in relation to others. Emotions can be defined as one of the engines that drive sportspeople to put all of themselves into these experiences, but only if properly managed they can bring that added value to those who practice sport. Thus it can be interpreted in pedagogical accent as the exercise of discipline trains in living up to commitments and the personality. The sports education through the training involves the psychophysical effort, and respect for rules and allows the athletes to know their limits and overcome them.